MRI detection of mild malformation of cortical development with oligodendroglial hyperplasia (MOGHE) on T1WI-CHESS - Elly Arizono; Zen-ichi Tanei; Keiya Iijima; Yukio Kimura; Yoko Shigemoto; Hiroyuki Maki; Midori Kusama; Kumiko Murayama; Masaki Iwasaki; Takashi Saito; Yuko Saito; Kazuhiro Saito; et al. (Epilepsy & Behavior Reports, 2024)
Mild malformation of cortical development with oligodendroglial hyperplasia (MOGHE) is a recently proposed epileptogenic entity that is difficult to detect on MRI. We present a case of MOGHE that was successfully detected on T1WI-chemical shift-selective saturation (CHESS) MRI. The clinical presentation, MRI including T1WI-CHESS, functional images, and pathology findings of a 14-year-old Japanese girl diagnosed with MOGHE are described. T1WI-CHESS revealed an abnormal high signal along the affected lesion, whereas the findings shown by the other MR sequences were less obvious; interictal fluorodeoxyglucose-positron emission tomography indicated slightly decreased accumulation in the lesion, and subtraction ictal single photon emission computed tomography co-registered to MRI showed an increased blood flow. Together these observations suggest that T1WI-CHESS may be a useful MR sequence for detecting the lesions in patients with MOGHE.